2017
DOI: 10.1002/mus.25992
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of acute motor axonal neuropathy and acute inflammatory demyelinating polyradiculoneuropathy in 140 children with Guillain–Barré syndrome in India

Abstract: AIDP is the most common GBS subtype in children. It is characterized by better recovery at 3 months when compared with AMAN. Muscle Nerve 57: 761-765, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
3
18
1
Order By: Relevance
“…Although this study does not only include severe Guillain-Barré syndrome patients, the overall mean hospital stay was 16 days, and it was 22 days in acute motor axonal neuropathy patients. 31 Electrophysiologic findings of all patients in our study group were consistent with acute motor axonal neuropathy, and the mean hospital stay of these patients was 18 days ( Table 1). Considering that our patients are more severe, it can be said that the zipper method fastens recovery time.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Although this study does not only include severe Guillain-Barré syndrome patients, the overall mean hospital stay was 16 days, and it was 22 days in acute motor axonal neuropathy patients. 31 Electrophysiologic findings of all patients in our study group were consistent with acute motor axonal neuropathy, and the mean hospital stay of these patients was 18 days ( Table 1). Considering that our patients are more severe, it can be said that the zipper method fastens recovery time.…”
Section: Discussionsupporting
confidence: 53%
“…30 In a prospective pediatric case series, it was reported that the most common type of Guillain-Barré syndrome is acute inflammatory demyelinating polyneuropathy and acute motor axonal neuropathy is associated with poor outcome. 31 Mechanical ventilation need was recorded in 24.2% and 13.7% of acute motor axonal neuropathy and acute inflammatory demyelinating polyneuropathy patients, respectively. Although this study does not only include severe Guillain-Barré syndrome patients, the overall mean hospital stay was 16 days, and it was 22 days in acute motor axonal neuropathy patients.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this setting, after 2 months of nadir, the clinical outcomes were better, as 46.9% complained of residual paralysis. It was reported that by the third month, 47.1% of GBS patients are expected to have a complete recovery, while 24.3% will have poor recovery (wheelchair-bound) 40. One longitudinal study stated that the rates of GBS patients with complete recovery or minor limitations was 41% in the first month, 71% in the third, 86% in the sixth, and 92% in the twelfth 41.…”
Section: Discussionmentioning
confidence: 99%